Minat dan Persepsi Pengguna Sampah Online Banyumas dalam Mengelola Minyak Jelantah - Asana, Mahila; Muttaqin, Akmal Ryan; A’idah, Reza Nur; Novitasari, Sandra; Setiawati, Indah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Environmental problems caused by poor household waste management, including used cooking oil, remain a serious issue in Indonesia. Disposing of used cooking oil improperly can pollute the environment and pose health risks. Banyumas Regency has developed the Sampah Online Banyumas (Salinmas) application to support waste management; however, the management of used cooking oil remains limited. This study aims to describe the attitudes, perceived behavioral control, and intentions of Salinmas users in managing used cooking oil. The research employed a descriptive quantitative method with a survey approach. A purposive sample of 142 active Salinmas users from four districts in Purwokerto was selected. Data were collected through questionnaires and analyzed using descriptive statistics. The results show that public attitudes toward used cooking oil management fall into the very high category, reflecting positive views on its environmental and social benefits. Perceived behavioral control is also very high, indicating strong confidence in the ease and ability to manage used cooking oil, especially with supporting facilities such as collection services. Meanwhile, the public’s intention is also categorized as high, indicating a strong interest in participating in management activities, including converting used oil into useful products. These findings suggest that the people of Banyumas have great potential to actively engage in sustainable used cooking oil management if supported by proper education and adequate facilities.